Amazing grace [videorecording (DVD)] - Pollack, Sydney, 1934-2008; Franklin, Aretha; Franklin, Aretha; Franklin, Aretha; Cleveland, James; Cleveland, James (Universal Pictures Home Entertainment, 2019)
Documentary presenting the live recording of the Aretha Franklin album.